Determining Purchasing Decisions and Customer Satisfaction based on Price and Trust: A Literature Review of Marketing Management - Hamdan, Hamdan; Ali, Hapzi; Rizky Mahaputra, M. (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The purpose of writing this Literature Review Paper is to determine the influence of price and trust variables on purchasing decisions and customer satisfaction. With qualitative methods and Library Research. The results of the study indicate that price influences purchasing decisions, advertising influences customer satisfaction, trust influences purchasing decisions, trust influences customer satisfaction and purchasing decisions influence customer satisfaction.